The Upside to Feeling Worse Than Average (WTA): A Conceptual Framework to Understand When, How, and for Whom WTA Beliefs Have Long-Term Benefits - Whillans, Ashley V.; Jordan, Alexander H.; Chen, Frances S. (Frontiers in Psychology, 2020)
Our thoughts, feelings, and behaviors are shaped in critical ways by our beliefs about how we compare to other people. Prior research has predominately focused on the consequences of believing oneself to be better than average (BTA). Research on the consequences of worse-than-average (WTA) beliefs has been far more limited, focusing mostly on the downsides of WTA beliefs. In this paper, we argue for the systematic investigation of the possible long-term benefits of WTA beliefs in domains including motivation, task performance, and subjective well-being. We develop a conceptual framework for examining these possible benefits, we explore the usefulness of this framework to generate novel insights in an important psychological domain (skill learning), and we conclude with broader recommendations for research in other domains such as friendship formation, moral, and political decision making.